2019
DOI: 10.1021/acs.jpcb.9b07654
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Phase Transitions of the Ionic Liquid 1-Ethyl-3-methylimidazolium Dicyanamide

Abstract: Several calorimetric measurements have shown that 1-ethyl-3-methylimidazolium dicyanamide, [C2C1im]­[N­(CN)2], is a glass-forming liquid, even though it is a low-viscous liquid at room temperature. Here, we found slow crystallization during cooling of [C2C1im]­[N­(CN)2] along Raman spectroscopy measurements. The low-frequency range of the Raman spectrum shows that the same crystalline phase is obtained at 210 K either by cooling or by reheating the glass (cold-crystallization). Another crystalline phase is for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Hamiltonian 23 as implemented in the MOPAC software. 24 More recently, it was shown that free energy surfaces of first coordination shell of ion pairs of ionic liquids obtained at DFT level produces results in excellent agreement with the ones obtained from liquid phase MD simulations, 25,26 demonstrating that even in some complex cases, Themis is able to probe the structure of condensed phases. This enables the comparison of forcefields with higher theory methods such as DFT, which are too costly to be applied even for small clusters.…”
Section: Resultsmentioning
confidence: 71%
“…Hamiltonian 23 as implemented in the MOPAC software. 24 More recently, it was shown that free energy surfaces of first coordination shell of ion pairs of ionic liquids obtained at DFT level produces results in excellent agreement with the ones obtained from liquid phase MD simulations, 25,26 demonstrating that even in some complex cases, Themis is able to probe the structure of condensed phases. This enables the comparison of forcefields with higher theory methods such as DFT, which are too costly to be applied even for small clusters.…”
Section: Resultsmentioning
confidence: 71%
“…The dispersion energy per ion pair is unaffected by the shear in the newtonian regime, but for very high shear rates it starts to increase. This behavior can also be described by the Carreau equation, which can be used to describe the dependence of several properties with g 0 , as will be shown in the following, by generalizing it to different properties A as in eqn (3), where A 0 is the zero shear value of A, and the other parameters hold the same meaning as discussed before with subscript ''A'' added to indicate that the values of fitting parameters may be different for different properties.…”
Section: C2 Structural Changes and Non-newtonian Behavior Under High ...mentioning
confidence: 99%
“…Most ionic compounds are crystalline solids at ambient temperature, with very high melting temperatures, due to strong electrostatic interactions between oppositely charged ions. However, the melting point can be lowered by the presence of bulkier, flexible and low symmetry ions, [1][2][3][4] such as salts with melting point smaller than 100 1C called ionic liquids (ILs). The ability to combine different pairs of cations and anions, as well as variations in their molecular structure, earned the ILs the title of ''designer solvents'', meaning that the physical properties may be tuned by changing the molecular structure if the correlation between them is known.…”
Section: A Introductionmentioning
confidence: 99%
“…The IL 1-ethyl-3-methyl-imidazolium dicyanamide, [C2C1IM][DCA], has two solid phases that differ from each other due to the in-plane or out-of-plane conformation of the cation ethyl group, as showed by Raman spectroscopy. 10 Computer simulations demonstrate that the conformation of the cation significantly changes the local spatial distribution of the anion. 8 The IL 1-butyl-3-methyl-imidazolium chloride, [C4C1IM] [Cl], has a monoclinic crystalline form with a gauche dihedral between the first and the second carbon of the butyl group and an orthorhombic form with the same dihedral in the trans conformation.…”
Section: Introductionmentioning
confidence: 99%